Carbon quantum dots modified MoS2 with visible-light-induced high hydrogen evolution catalytic ability. (April 2016) - Zhao, Shunyan; Li, Chuanxi; Wang, Liping; Liu, Naiyun; Qiao, Shi; Liu, Beibei; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract: We developed a facile hydrothermal method to fabricate the carbon quantum dots (CQDs)/MoS2 composite as hydrogen evolution reduction (HER) catalyst. After irradiation with visible light for 30 min, the CQDs/MoS2 composite (as CQDs/MoS2 -L30) performed improved HER activity, featured by a small overpotential of ∼0.125 V at 10 mA cm −2, a high current density, a small Tafel slope of 45 mV/decade and a long term stability in 0.5 M H2 SO4 . This kind of activity improvement towards HER may be due to the high charge transfer efficiency, the decrease of S 4+ and the increase of S 2 2 − and S 2− after the light treatment.